Natural recreation and tourist resources of the Podilia region - Yavorska, Victoria; Kolomiyets, Kateryna; Dianova, Diana; Usatenko, Olena; Karabadgak, Panas (Journal of Education, Health and Sport, 2018)
In the presented publication are analyzed natural tourist resources of the Podilia region. The ball estimation of natural resources is conducted for to the science-geographical areas. It is distinguished the most favorable and the least favorable science - geographical areas for recreation and tourist activity.